Lung transplant list withdrawal in a liver transplant patient thanks to elexacaftor-tezacaftor-ivacaftor: a case report - Arianna Traunero; Anna Galletti; Sergio Ghirardo; Egidio Barbi; Massimo Maschio (BMC, 2024)
Abstract Background Elexacaftor-tezacaftor-ivacaftor (ETI) is a transmembrane conductance regulator modulator that significantly improves lung function in patients affected by cystic fibrosis (CF). This triple drug is currently not indicated in liver transplant patients, as clinical trials including subjects with previous solid organ transplantation are lacking. Case presentation We report on a liver transplant girl with CF-related advanced pulmonary disease meeting clinical criteria for lung transplant, who started the triple modulator because she could not get on the lung transplant waiting list due to psycho-social motivations. Since initiation of ETI therapy, she has experienced a significant improvement in respiratory function and quality of life, without adverse effects. Conclusions This case shows that ETI therapy can represent a lifesaving drug for individuals without alternatives, even in liver transplant patients. The clinical benefits of the modulator overcome risks, which may be limited with a close drug monitoring of immunosuppressants serum levels and functional liver tests.